Exploring the Critical Thinking Development Process of Supply Chain (Critical Thinking Skill and Tendency toward Critical Thinking) in Students (Case Study: Tabriz University) - Skandar FathiAzar; Yousef Adib; Rahim BadriGargari; Mohsen Koushafar (International Journal of Supply Chain Management, 2018)
The present study was done for studying the critical development process (tendency toward critical thinking and critical thinking skill) in students of general groups of Tabriz University. The method of present research, from goal perspective, was practical, and from identity perspective, it was descriptive-survey. Cluster and random sampling method was used for selecting the researchs samples about 341 people. The research tool included questionnaire attended to the California Critical Thinking of supply chain. For analyzing the accessed data from questionnaire, descriptive statistical tests and one-way variance analysis and schematic follow up test and independent t-test were used. The findings showed that the critical thinking development of supply chain (the critical thinking skill and tendency toward critical thinking) of students of general groups of Tabriz University in first, second, third and fourth years were different and included development and increasing process, and also there was difference between girls and boys in the critical thinking skill, but there was not difference in the tendency toward critical thinking of supply chain.